2017
DOI: 10.1111/ped.13182
|View full text |Cite
|
Sign up to set email alerts
|

Yield and complications of kidney biopsy over two decades in a tertiary pediatric center

Abstract: Kidney biopsy is an efficient and safe procedure in both native and transplanted kidneys and provides helpful diagnostic information in most cases in which it is deemed necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…With regard to the size and age of the patient, the degree of complications can be reduced by selecting the appropriate needle size and the limiting biopsy attempts. Performing biopsies by radiologists or nephrologists is another cause of the difference in the frequency of the complications (20). The results of the meta-analysis by Varnell et al showed that biopsy in children is safe, since only 11% of patients had hematuria and less than 1% needed blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the size and age of the patient, the degree of complications can be reduced by selecting the appropriate needle size and the limiting biopsy attempts. Performing biopsies by radiologists or nephrologists is another cause of the difference in the frequency of the complications (20). The results of the meta-analysis by Varnell et al showed that biopsy in children is safe, since only 11% of patients had hematuria and less than 1% needed blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…9 In another study, only (3/30) cases had complications like pneumonia secondary to i m m o b i l i s a t i o n , p e r i t o n i t i s a n d m i n i m a l parenchymal haemorrhage in each of the cases. 10 Similarly, in yet another study, the most common indication for renal biopsy was nephrotic syndrome (34.7%), followed by nephritic nephrotic syndrome (20%). Minimal change disease was the commonest pathological findings among nephrotic syndrome a n d a m o n g n o n -n e p h r o t i c p r i m a r y glomerulonephritis, IgA nephritis was the commonest findings.…”
Section: Discussionmentioning
confidence: 83%
“…After the removal of duplicates, 5004 unique records were identified, of which 4814 records were excluded after the screening of titles and abstracts. Of the 190 remaining studies, 72 studies (40 082 biopsies) 2,3,9,14,25-92 were included in the systematic review and meta-analysis after full-text review (Figure 1) including 4 single-center randomized controlled trials, 3 multicenter cohort studies (1 mixed retrospective-prospective and 2 retrospective), and 65 single-center cohort studies (10 prospective, 1 mixed retrospective-prospective, 46 retrospective, and 8 unreported). Details of the included studies are presented in Table S1, SDC, http://links.lww.com/TP/C332.…”
Section: Resultsmentioning
confidence: 99%